Can we rely on procalcitonin in the diagnosis of late onset neonatal sepsis?. (7th June 2011) - Athiraman, N; Agarwal, R; Krishnamoorthy, S; Guy, M
Abstract : Aims: (1) To explore the usefulness of procalcitonin (PCT) assay in the diagnosis of late onset neonatal sepsis (LONS). (2) To compare the diagnostic usefulness of PCT with C reactive protein (CRP). Methods: Infants ≥ 48 h old and being investigated for LONS were recruited after informed consent. The sepsis episodes were categorised into three groups: true positive, true negative and possible sepsis on the basis of clinical symptoms, results from blood culture or other sterile body fluids and raised CRP or thrombocytopenia. Results: A total of 219 sepsis episodes in 121 infants were evaluated. There were 79 (36%) true positive, 68 (31%) possible sepsis and 71 (33%) true negative episodes of sepsis. The sensitivity and specificity were calculated for true positive versus true negative episodes; and the cut-off used for CRP and PCT was 10 and 0.5 respectively. The sensitivity of PCT and CRP was 68% and 56% respectively whereas the specificity was 60% and 85% (table 1 ). Conclusion: PCT is a useful marker of LONS. In this study, PCT is more sensitive but less specific than CRP in the diagnosis of LONS. PCT could be used as a useful adjuvant to CRP in the evaluation of LONS.